2007
DOI: 10.5334/pb-47-3-173
|View full text |Cite
|
Sign up to set email alerts
|

Fear Appeal in Traffic Safety Advertising: The moderating role of medium context, trait anxiety, and differences between drivers and non-drivers

Abstract: The impact was investigated of the intensity of a fear appeal, the valence of the medium context, and the individuals' trait anxiety and personal relevance on the responses of 197 individuals to anti-speeding advertisements. A high level of fear attracts more attention. A negative valence context leads to a more positive anti-speeding attitude. The most important moderating effect of trait anxiety is that the attitude is more positive when low-anxiety individuals are exposed to high fear appeals in a context w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 45 publications
0
14
0
1
Order By: Relevance
“…This study did not explicitly focus upon possible interaction effects between message and context factors and evoked fear and cognitive appraisal effects. Nevertheless, they may be meaningful (see, for instance, Janssens and De Pelsmacker, 2007). The effect of the threat level of the context on evoked fear, threat, occurrence or efficacy may, for instance, be only visible at high or low levels of message threat, as found in this study.…”
Section: Discussion Conclusion and Further Researchmentioning
confidence: 89%
See 2 more Smart Citations
“…This study did not explicitly focus upon possible interaction effects between message and context factors and evoked fear and cognitive appraisal effects. Nevertheless, they may be meaningful (see, for instance, Janssens and De Pelsmacker, 2007). The effect of the threat level of the context on evoked fear, threat, occurrence or efficacy may, for instance, be only visible at high or low levels of message threat, as found in this study.…”
Section: Discussion Conclusion and Further Researchmentioning
confidence: 89%
“…This has been attributed to affective priming and excitation transfer (Kamins et al, 1991;Tavassoli et al, 1995;Yi, 1990). For instance, Faseur and Geuens (2006) found that for positive emotions the most effective ads are those that are shown in contexts evoking the same specific emotions as the ad, and Janssens and De Pelsmacker (2007) also found that the context was relevant for the responses to threat appeals.…”
Section: H1mentioning
confidence: 92%
See 1 more Smart Citation
“…Diğer bir deyişle bu fark henüz sürücü koltuğuna oturmamış ve sürücü olmanın içsel ve dışsal dinamikleriyle tanışmamış olmalarından dolayı olabilir. Bunu doğrular nitelikteki bir başka çalışmada hız sınırlarına uymakla ilgili bir reklam kampanyasının sürücüler ve sürücü olmayanlar üzerine etkisini inceleyen bir araştırmada sürücüler ile sürücü olmayanların odaklandıkları noktaların farklı noktalar olduğu; sürücü olmayanların sürüşle ilgisi olmayan kısımlara daha çok odaklandığı bulunmuştur (Janssens ve De Pelsmacker, 2007). Bu nedenle belki de sürücü olmayan kişiler, hız yapmanın nedeni olarak gösterilen sebepleri değerlendirmektense kendileriyle ilgili başka bilgileri (örn; trafik harici ortamlardaki davranışları) değerlendirmeye almaktadır ve trafiğe çıktıklarında kurallara uyacakları yönünde olumlu beyanda bulunmaktadır.…”
Section: Discussionunclassified
“…This suggests that pre-existing practices, and presumably prior decisions to smoke or refrain from smoking, led people either to accept or reject the message. Leventhal [97] review a number of studies showing that vulnerable people (e.g., smokers) were less amenable to fear appeals than invulnerable people [80,85,99].…”
Section: Starting Pointsmentioning
confidence: 99%